Mastering regular expressions - Friedl, Jeffrey E. F. (Sebastapol, CA : O'Reilly, 2007)
A regular expression (regex) is a pattern that describes a set of strings. Regular expressions are used for advanced context-sensitive searches (e.g. parsing data streams, data mining) and text modifications. They can be found in many advanced editors (e.g. vi, Emacs), in parser programs (e.g. grep) and in languages (e.g. Perl), mostly in a UNIX environment. This book is the standard work on regexes.
Previous ed.: 2002.
Includes index.
Keywords: Text processing (Computer science); Perl (Computer program language); Computer programming